Effects of Price, Information, and Transactions Cost Interventions to Raise Voluntary Enrollment in a Social Health Insurance Scheme: A Randomized Experiment in the Philippines. (1st December 2015) - Capuno, Joseph J.; Kraft, Aleli D.; Quimbo, Stella; Tan, Carlos R.; Wagstaff, Adam
Abstract: A cluster randomized experiment was undertaken testing two sets of interventions encouraging enrollment in the Individually Paying Program (IPP), the voluntary component of the Philippines' social health insurance program. In early 2011, 1037 unenrolled IPP‐eligible families in 179 randomly selected intervention municipalities were given an information kit and offered a 50% premium subsidy valid until the end of 2011; 383 IPP‐eligible families in 64 control municipalities were not. In February 2012, the 787 families in the intervention sites who were still IPP‐eligible but had not enrolled had their vouchers extended, were resent the enrollment kits and received SMS reminders. Half the group also received a 'handholding' intervention: in the endline interview, the enumerator offered to help complete the enrollment form, deliver it to the insurer's office in the provincial capital, and mail the membership cards. The main intervention raised the enrollment rate by 3 percentage points (ppts) ( p  = 0.11), with an 8 ppt larger effect ( p  < 0.01) among city‐dwellers, consistent with travel time to the insurance office affecting enrollment. The handholding intervention raised enrollment by 29 ppts ( p  < 0.01), with a smaller effect ( p  < 0.01) among city‐dwellers, likely because of shorter travel times, and higher education levels facilitating unaided completion of the enrollment form. Copyright © The World Bank Health Economics © 2015 John Wiley & Sons, Ltd.